Effect of copper/nickel ratio on the efficiency of biobeneficiation of bulk copper-nickel sulfide concentrates. (31st May 2022) - Muravyov, Maxim; Panyushkina, Anna; Fomchenko, Natalya
Highlights: The difference in rest potentials is used for biobeneficiation of bulk concentrates. Obtaining a copper concentrate depended on chalcopyrite content in bulk concentrate. The rate of nickel sulfide bioleaching did not depend on the content of chalcopyrite. Abstract: The dependence of the efficiency of biobeneficiation (via bioleaching) of bulk copper-nickel sulfide concentrates on the ratio of copper to nickel sulfide minerals was studied. The copper content in the concentrates ranged from 10.8 to 19.1% (copper occurred in chalcopyrite), while the content of nickel was within 4.6–9.5% (nickel occurred in pentlandite and violarite). Although the copper content was higher than the content of nickel in all concentrates, the rate of nickel leaching significantly exceeded that of copper leaching. For the concentrates characterized by copper/nickel ratio ( k ) equal to 1.15 and 1.5, the average nickel leaching rate was ˃8 times higher than the copper leaching rate. Bioleaching of all studied concentrates allowed the obtainment of copper concentrates in solids (copper content of 15.6–18.7%) in which nickel content was low (0.27–1.49%). The high level of nickel dissolution and the maximum increase in the copper content in the solids were shown for the concentrate with the initial copper and nickel content of 10.9 and 7.2%, respectively ( k of 1.5). In this bioleach residue, the copper content increased by 4.7%, while the nickel content decreased by 6.86% compared to the original concentrate. Thus, bioleaching of copper-nickel concentrates can be considered biobeneficiation, and the highest efficacy of the process may be achieved at a copper/nickel ratio of ∼1.5.